الجرائم المرتكبة عبر الوسط الإلكتروني في ضوء الشريعة الإسلامية والتشريع الإماراتي بالتركيز على جرائم القذف والابتزاز : Crimes Committed Via the Electronic Medium in The Light of Islamic Law and Emirati Legislation Focusing on Defamation and Extortion Crimes - Alameeri, Ahmed Esmail; Hussin , Syaryanti (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
تناولت الدراسة اقتراحاً علمياً وأكاديمياً حول موضوع الجرائم المرتكبة عبر الوسيط الإلكتروني، والمعالجات القانونية لهذه الأنواع من الجرائم. وهدفت إلى توضيح أشكال وصور جرائم القذف والابتزاز من خلال الوسط الالكتروني في الشريعة الإسلامية من خلال عرض الآراء الفقهية وتوضيح الآثار القانونية الناتجة عن تلك الجرائم المرتكبة من خلال الوسط الالكتروني، وبيان المعالجة القانونية لها في القانون الإماراتي، وكذلك الشرح والتحليل لمفهوم جريمة الابتزاز الالكتروني والدوافع من وراء ارتكاب تلك الجريمة، والآثار القانونية الناتجة عن تلك الجريمة. واتبع المنهج الوصفي التحليلي والمقارن، لوصف الظاهرة وتحليلها من جميع أبعادها وجوانبها، وقد خلصت إلى عدة نتائج أهمها بيان التفرقة بين السياسة الجنائية العامة الواردة في قانون العقوبات وبين ما تحتاج إليه هذه الجرائم من سياسة جنائية مختلفة سواء تجريما أو عقابا، كذلك تنبه المشرع الاماراتي لهذا الاختلاف في النموذج الإجرامي لهذه الجرائم ووسائلها وفاعلها وبالجملة ذاتيتها عن مثيلاتها التقليدية وإن تشابها في الهدف والمبتغى. The study dealt with a scientific and academic proposal on the topic of crimes committed through the electronic medium, and legal treatments for these types of crimes. It aimed to clarify the forms and images of defamation, fraud, and extortion crimes through the electronic medium in Islamic law by presenting jurisprudential opinions and clarifying the legal effects resulting from those crimes committed through the electronic medium, and clarifying the legal treatment thereof in UAE law, as well as explaining and analyzing the concept of the crime of electronic extortion and motives Who is behind the commission of that crime, and the legal implications resulting from that crime. It followed the descriptive, analytical and comparative approach, to describe and analyze the phenomenon from all its dimensions and aspects. It has reached several results, the most important of which is a statement of the distinction between the general criminal policy contained in the Penal Code and what these crimes need in terms of a different criminal policy, whether criminalization or punishment. The UAE legislator also alerted this the difference in the criminal model of these crimes, their means, their perpetrator, and their very nature from their traditional counterparts, even if they are similar in purpose and purpose.